Caso clínico 02-2018. Mujer 76 años con cefalea, dolor articular y disfagia de rápida instauración - Vásquez Kunze, Sergio; Cruz-Encarnación, María; Cok García, Jaime; Calvo Quiroz, Armando (Revista Médica Herediana, 2018)
.